2023
DOI: 10.1021/acs.jpclett.2c03591
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of Chemical Dopants in Simulated Resonance Raman Spectroscopy of Carbon Nanotubes

Abstract: Single-walled carbon nanotubes (SWCNTs) with organic sp 2 or sp 3 hybridization defects allow the robust tunability of many optoelectronic properties in these topologically interesting quasi-one-dimensional materials. Recent resonant Raman experiments have illuminated new features in the intermediate-frequency region upon functionalization that change with the degree of functionalization as well as with interactions between defect sites. In this Letter, we report ab initio simulated near-resonant Raman spectro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 77 publications
3
8
0
Order By: Relevance
“…Figure 2 shows close agreement between their data and our deduced frequencies, suggesting that the IFM band is a defect-induced feature of the nanotube itself and is not specific to the method or reaction used to introduce defects. The data in Figure 2 strongly support the findings of Weight et al 28 who used the coupled perturbed Hartree−Fock (CPHF) method with different laser wavelengths to simulate the defect-induced IFM Raman features. The results of their calculations showed that Raman spectra depend strongly on whether the incident photon couples to the E 22 or E 11 transition.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…Figure 2 shows close agreement between their data and our deduced frequencies, suggesting that the IFM band is a defect-induced feature of the nanotube itself and is not specific to the method or reaction used to introduce defects. The data in Figure 2 strongly support the findings of Weight et al 28 who used the coupled perturbed Hartree−Fock (CPHF) method with different laser wavelengths to simulate the defect-induced IFM Raman features. The results of their calculations showed that Raman spectra depend strongly on whether the incident photon couples to the E 22 or E 11 transition.…”
supporting
confidence: 83%
“…They therefore suggested that multiple Raman laser wavelengths are needed to provide a complete view of nanotube phonons. 28,29 For E 22 S excited SWCNTs, we found that our data fit well to the following empirical relation between IFM frequency (ν IFM ), nanotube diameter (d t ), and incident photon frequency (v L ):…”
supporting
confidence: 59%
See 1 more Smart Citation
“…The top right panel (above Figure c,d) provides the real-space projected bare electronic transition density of the ground-to-E 11 state exciton, demonstrating its delocalized excitation character. Semiconducting SWCNTs, when functionalized with covalent adducts forming a hybridization defect, exhibit bright emission features due to the addition of a defect-associated exciton below the band edge, which have been the subject of much experimental and theoretical work over the past decade for their use as single-photon light sources and for their tunable emission at low-energy telecommunications wavelengths. The simplicity of this system’s dipole matrix (akin to a two-level system) will lead to clear theoretical predictions and a new pathway toward the tunable manipulation of SWCNTs by coupling to optical cavities, without the need for chemical functionalization.…”
mentioning
confidence: 99%
“…Single-walled carbon nanotubes (SWCNTs) functionalized with a single or multiple sp 3 -hybridized defects (each consisting of a covalent bond of two groups on a single carbon ring) are regarded as excellent sources of single photons at room temperature. ,, This makes them useful for applications in quantum circuits as well as in telecommunications and other technologies relying on highly tunable single-photon emission. Much recent theoretical work has been done exploring the structure–property relationships in these systems from the point of view of the Condon geometry. ,,,, However, control over the dynamic processes following electronic excitation has only loosely been discussed from the theoretical side. A better understanding of these processes, such as carrier trapping and detrapping, , Auger recombination, , and exciton redistribution/diffusion, ,, would give insight into further tunability and control of these systems’ optical and spintronic properties. Recent experimental results characterizing the photoluminescence dynamics ,, in these systems inspires state-of-the-art simulations. In this study, we explore nonradiative relaxation processes in a variety of SWCNT chiralities and single-defect functionalization chemistries to elucidate the structure-dependent tunability of the exciton relaxation into the energetically low-lying emitting state associated with the defect.…”
mentioning
confidence: 99%